The ontogency of the genital system of Elisolimax flavescens (Keferstein) (Pulmonata, Urocyclidae) - Nel, N. E (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1981.